2022
DOI: 10.9734/ajmah/2022/v20i11759
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Liver Histomorphology, Hematological Parameters and Lipid Profile of Cadmium-Exposed Rats Treated with Combined Leaf Extract of Vernonia amygdalina and Occimum gratissimum

Abstract: Aim: This study was aimed at examing the effect of mixture of Ocimum gratissimum extract and Vernonia amygdalina extract on lipid profile and hematological parameters of Wistar rats administered with cadmium. Methodology: Sixteen female rats were divided into four groups and designated as follows: Group 1-Control (Normal Saline,) Group 2-(Cadmium 10mg/kg bwt), Group 3 (Normal saline, leaf extract 200kg/kg bwt) Group 4 (Cadmium 10mg/kg bwt and leaf extract 200kg/kg bwt) and were treated for 28 days (4 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Earlier reports by Abarikwu and others suggested that atrazine may have an immunosuppressive impact [21]. This outcome is similarly consistent with that reported by Udi et al [22] who also noted splenic cell degeneration in response to garlic extract. This may be caused by an increase in the rate of erythrocyte breakdown following pesticide exposure [23,24].…”
Section: Spleen Histopathological Alterationssupporting
confidence: 89%
“…Earlier reports by Abarikwu and others suggested that atrazine may have an immunosuppressive impact [21]. This outcome is similarly consistent with that reported by Udi et al [22] who also noted splenic cell degeneration in response to garlic extract. This may be caused by an increase in the rate of erythrocyte breakdown following pesticide exposure [23,24].…”
Section: Spleen Histopathological Alterationssupporting
confidence: 89%
“…14 The ethanol leaf extracts of O. gratissimum and Vernonia amygdalina have also been investigated for their potential to ameliorate the lipid profile, haematology and histomorphology of cadmium-exposed rats. 15 In other related studies, the oxidative damage induced by lead acetate in lymphoid tissues and haematological parameters of adult Wistar rats was improved by administering the ethanol leaf extract of O. gratissimum, 16 while the methanolic leaf extract of O. gratissimum has also been studied for its ability to attenuates oxidative stress and liver injury in gentamicininduced hepatotoxicity in rats. 17 O. gratissimum is a perennial and herbaceous plant.…”
Section: Introductionmentioning
confidence: 99%